Pengaruh Pendekatan Spritual (Murottal) Tehadap Penurunan Tingkat Stress Pada Perawat di RSUD Kabupaten Natuna - Sri Muharni; Utari Christya Waradhani; Dini Wuri Puji Puryati (Jurnal Ventilator, 2023)
Hospital nurses, especially IGD and ICU, are required to be able to work quickly and precisely in dealing with emergency patients with different emergency levels, so they are very vulnerable to work stress. One way to cope with the work stress of IGD and ICU nurses is to listen to murottal which is one type of religious therapy. The purpose of this study was to find out the effect of murottal therapy on reducing nurse stress levels. The study used the quasi-experimen method of intervention groups and control groups. The population of this study is IGD and ICU nurses at Natuna Regency Hospital. Total sampling sample of 24 nurses who fit the Inclusion criteria. The measuring instrument used is the DASS 42 Stress quisioner. The results showed that t counted 4,662 > t table 2,064 so that it could be concluded that murottal therapy had an effect on reducing the stress level of nurses at Natuna Regency Hospital. The researchers hope that a spiritual approach can be applied in hospitals. To better find out the greater effect of murottal therapy on reducing nurse stress levels, it is hoped that future studies can use larger and more comprehensive samples in all rooms in the hospital.